EVALUATING FINANCIAL PERFORMANCE OF PT. PLAZA INDONESIA REALTY TBK - Sriratna, I Dewa Ayu Raka (Jurnal Berkala Ilmiah Efisiensi, 2016)
The financial performance of company can be seen by the financial statements. By the financial statement of company, it can be the informationand helped the investor to analyze the company financial position and also for the top management of the company to make a business decision. This research aims to find out the financial performance of PT. Plaza Indonesia Realty Tbk by using financial ratio and DuPont analysis. The type of this research is quantitative descriptive research and the data were gathered from financial statements of PT. Plaza Indonesia Realty Tbk from 2011 to 2015. Based on the result of data analyzed, PT. Plaza Indonesia Realty Tbk has good financial performance. It can be seen by the ratio that above than the standard ratio. Based on the value of the ratio, PT. Plaza Indonesia Realty Tbk reached its best financial performance in 2014. It can be seen from the value of all financial ratios from 2011 - 2015.